Design development and optimization of immediate release tablet of valsartan - Sharma, Abhimanyu Rai; Shrivastava, Birendra; Bhargava, Anurag; Sharma, Shailesh; Raina, Binu; Bajwa, Prabhjot Singh (Journal of Drug Delivery and Therapeutics, 2019)
The objective of the present study was to prepare immediate release tablets (IRTs) of valsartan by direct compression method. Two types of superdisintegrants i.e. sodium starch glycolate (SSG) and Ac-Di-sol were used in the formulation of tablets. Twelve preliminary trial batches were prepared by varying the concentration of superdisintegrants. It was found that formulation containing Ac-Di-Sol disintegrated in less time as compared to formulation containing sodium starch glycolate. Values of friability was found to be more in case of formulation containing Ac-Di-Sol. Attempts were also made to prepare the tablets containing superdisintegrants in combination and these resulted in the formulation with improved values of disintegration time and friability. On the basis of preliminary studies optimization of IRT was done employing 32 full factorial design using design expert 7. The optimized batch of IRTs showed friability and disintegration time values of 0.82 ± 0.07 and 29 ± 1 respectively. The percent release was also found to be 94.73 ± 4.97% in 5 min. Keywords: Immediate release tablets, Valsartan, Hypertension, Sodium starch glycolate, Ac-Di-Sol, 32 full factorial design